Wealthy Tax Non-Filers in a Developing Nation: The Roles of Taxpayer Knowledge, Perceived Corruption and Service Orientation in Pakistan - Katharina Gangl; Erich Kirchler; Christian Lorenz; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2015)
Although tax non-filing and the resulting tax evasion are a challenge to public welfare of developing countries, scholarly knowledge on the subject is minimal. The present paper compares rich self- employed identified as non-filers with a randomized group of tax filers in terms of two bases of perceived tax system legitimacy: knowledge of taxpayers' rights and perceived corruption. The results indicate that both factors relate to tax non-filing and moreover, that perceived service orientation of the tax administration, which reduces citizens' ignorance of tax rights and doubts about authorities' correct behaviour might foster perceived legitimacy and in turn increase tax compliance.
Keywords: H26; O17; E26; H70; I30; 330; Wealthy tax non-filers; tax morale; tax compliance; tax knowledge; knowledge of rights; corruption; tax evasion; developing countries; Pakistan